Interaction of an argon plasma jet with a silicon wafer. (3rd March 2016) - Engelhardt, Max; Pothiraja, Ramasamy; Kartaschew, Konstantin; Bibinov, Nikita; Havenith, Martina; Awakowicz, Peter
Abstract: A filamentary discharge is ignited in an argon plasma jet under atmospheric pressure conditions. The gas discharge is characterized with voltage-current measurements, optical emission spectroscopy and an ICCD-camera with a high temporal resolution down to 10 ns. In the effluent of the plasma jet, filaments come into contact with the surface of a silicon wafer and modify it, namely etching traces are produced and microcrystals are deposited. These traces are studied with optical and electron microscopes. The material of the deposited microcrystals and the surface modifications of the silicon wafer are analyzed with Raman microspectroscopy. Amorphous silicon is found within the etching traces. The largest part of the deposited microcrystals are composed of nitratine (NaNO3 ) and some of them are calcite (CaCO3 ). Analyzing the possible reasons for the silicon wafer modifications we come to the conclusion that plasmoids, which are produced near the substrate surface by interaction with ionization waves, are a plausible explanation for the observed surface modifications of the silicon wafer.